Geriatric Patient with Osteoarthritis and Obesity Survived from Critically Ill of COVID-19: A Case Report - Budi Yanti; Mauliza Mauliza; Novita Andayani (Faculty of Medicine Universitas Airlangga, 2021)
Introduction: The Corona Virus Disease (COVID-19) pandemic has become a major problem worldwide. Currently, the group of geriatrics always coincidence with chronic diseases like hypertension, diabetes mellitus, and osteoarthritis discovered with a general level of severity, disability and even death. In addition, obesity is associated with several high risks of disease severity and worse clinical outcome in COVID-19.Case: a geriatric patient with comorbidities of osteoarthritis and obesity class 1 suffered from critically ill COVID-19. Clinical manifestations that were atypical and without a history of epidemiology made it difficult to screen for COVID. Furthermore, it was found that the respiration rate, heartbeat, and blood pressure increased, oxygen saturation was only 86%, crackles all over the right lung, chest x-ray showed bilaterally infiltrates and reverse transcriptase-polymerase chain reaction (RT-PCR) test showed positive severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) on admission. Patients managed with high flow nasal canulla (HFNC) flow 40 lpm and FiO2 78% with temperature 370C, selection of appropriate hydrophilic antibiotic such moxifloxacin iv and antiviral therapy. Obesity-related calorie regulation is given according to The Indonesian Association of Clinical Nutritionists (PDGKI), osteoarthritis medicationis still provided during the treatment resulted in a very good clinical progress. Furthermore, the patient finally recovered and was allowed to go home on the 13th day of treatment with maximum improvement.Conclusion: It is very important for clinicians to know the complex therapy management of patients in the geriatric group. This is because this population generally had atypical clinical symptoms and those that were admitted to the hospital already had severe cases.